Hospital infections on the basis of microbiologic study in surgical wards Wł. Biegański Hospital in Jędrzejów - Dutkiewicz, Sławomir A.; Romek, Ewa (Przewodnik Lekarza/Guide for GPs, 2009)
Hospital infections are a serious problem of contemporary medicine. The authors of the study presents identify hospital patogenes and their sensitivity to drugs in surgical wards Wł. Biegański Hospital in Jędrzejów. The most frequently isolated microbs from urinary tract infections was Escherichia coli. Analysis the frequency in relation to clinical forms of the infection the most frequent were urinary tract and respiratory tract and too surgical wound infections. Also in paper reporting many aspects to hospital infections and prevention of hospital infections methods.